PEMETAAN STRUKTUR BIDANG ILMU MENGGUNAKAN ANALISIS JEJARING SOSIAL: PERUBAHAN BIDANG ILMU PUBLIKASI PENELITIAN KELAUTAN DAN PERIKANAN INDONESIA - Rahmaida, Rizka (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2017)
Indonesia is a maritime country with two-third of its total area consist of water. Research on marine and fisheries studies should be considered as an important matter in Indonesia. Studies on research development can be a way to evaluate and to determine research policy direction. The increasing of scientific publication database draws the need for enhancement to their quantitative techniques analysis to understand research structure; social and science structure. This study aims to map the subject area, that covered research on marine and fisheries studies and carried out by institution located in Indonesia. Social network analysis is used to show the relationship of subject area in the related research. Data that is used in this research is based on marine and fisheries studies that conducted in Indonesia and indexed by Scopus for the last ten years (2006-2015). The network map shows that the publication has changed in terms of the covered subject areas and the relationship among them. The result of this study can be used to evaluate and to support marine and fisheries research policy direction in Indonesia.